The variational homotopy perturbation method for solving the K(2,2)equations - Bouhassoun, Abdelkader; Zellal, Mohamed (International Journal of Applied Mathematical Research, 2013)
This paper deals with implementation of the variational homotopy pertubation method (VHPM) for solving the K(2,2) compacton equation. The numerical results show that the approach is easy to implement and accurate whenit is compared with the exact solution. The suggested algorithm is quite efficient and is practically well suitedfor use in the nonlinear problems. The fact that the proposed technique solves nonlinear problems without usingthe Adomian's polynomials can be considered as a clear advantage of this algorithm over the decomposition method.